2017
DOI: 10.1016/j.kint.2017.03.053
|View full text |Cite
|
Sign up to set email alerts
|

The role of trimethylamine N-oxide as a mediator of cardiovascular complications in chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) have an enhanced risk of cardiovascular (CV) morbidity and mortality when compared to age and gender- Cardiovascular disease in CKD -Unexplained riskPatients with chronic kidney disease (CKD) have an enhanced risk of cardiovascular (CV) morbidity and mortality when compared to age and gendermatched individuals with normal kidney function. 1 Advanced kidney disease (stage G5A3; estimated glomerular filtration rate (eGFR) <15 mL/min/1.73m 2 , albumin:creatinine ratio >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 50 publications
2
63
0
4
Order By: Relevance
“…Notably, trimethylamine N-oxide is a gut-derived amine oxide that has been implicated in the etiology of CVD in the normal population 25 and in patients with CKD. 26 Second, intestinal dysbiosis partly accounts for the impaired barrier function of the intestinal epithelium, resulting in the translocation of bacterial fragments through the bowel wall. In the past few years, numerous studies have shown that translocated bacterial fragments play important roles in the pathogenesis of uremic toxicity, inflammation, insulin resistance, protein-energy wasting, and progression of CKD, and are an important nontraditional cardiovascular risk factor in CKD.…”
mentioning
confidence: 99%
“…Notably, trimethylamine N-oxide is a gut-derived amine oxide that has been implicated in the etiology of CVD in the normal population 25 and in patients with CKD. 26 Second, intestinal dysbiosis partly accounts for the impaired barrier function of the intestinal epithelium, resulting in the translocation of bacterial fragments through the bowel wall. In the past few years, numerous studies have shown that translocated bacterial fragments play important roles in the pathogenesis of uremic toxicity, inflammation, insulin resistance, protein-energy wasting, and progression of CKD, and are an important nontraditional cardiovascular risk factor in CKD.…”
mentioning
confidence: 99%
“…TMA is further oxidized by hepatic enzymes flavin monooxygenases 3(FMO3) in the host liver and generates TMAO, which is the end product and cannot be metabolized further (). The majority of TMAO can be excreted unchanged in the urine by the kidney within 24 h (). The remaining TMAO is reduced to TMA by the action of TMAO reductase () (Fig.…”
Section: Production and Metabolism Of Tmaomentioning
confidence: 99%
“…Therefore, an imbalance in gut microbiota could increase plasma TMAO levels in patients with CKD and aggravated renal function impairment [5]. Furthermore, studies have shown that safe and well-tolerated therapeutic interventions, such as the use of probiotics to improve the gut microbiota, can reduce TMAO levels in the body and mitigate its cardiovascular and renal damage [6][7][8]. Accordingly, investigating methods to reduce TMAO levels in the body will be of great significance in delaying the development of cardiovascular and renal diseases [1,2].…”
Section: Ivyspringmentioning
confidence: 99%